The Federal Road Through Georgia, the Creek Nation, and Alabama, 1806-1836 - Southerland, Henry deLeon (Book collections on Project MUSE., 2014)
Normal0falsefalsefalseMicrosoftInternetExplorer4 The Federal Road was a major influence in settlement of the Mississippi Territory during the period between the Louisiana Purchase and removal of the Creek Indians. Histories of early Alabama covering this period are replete with references to isolated incidents along the Federal Road but heretofore no documented history drawn from original sources has been published. Authors Southerland and Brown have explored many scattered and often obscure sources in order to produce this fascinating, informative account of the imp.